Deprescribing benzodiazepines among hospitalised older adults: quality improvement initiative - Frances Carr; Peter Tian; Jeffrey Chow; Jennifer Guzak; Jean Triscott; Pamela Mathura; Xing Sun; Bonnie Dobbs (BMJ Open Quality)
Benzodiazepines are recognised as being potentially inappropriate medications for seniors due to their considerable side-effect profile, yet they are commonly prescribed and infrequently discontinued (deprescribed). The study’s primary objective was the deprescription or the dose reduction of benzodiazepines among newly hospitalised seniors using a patient education intervention. A 3-month duration quality improvement study based on the plan–do–study–act model was conducted across two units (3C and 4D) in the Glenrose Rehabilitation Hospital to improve benzodiazepine deprescribing among newly admitted seniors (65 years or older) who were using benzodiazepines. The primary outcome measure was the number of eligible patients who had benzodiazepine deprescribing initiated. A patient education intervention comprising a structured medication review, written patient education (the Eliminating Medications Through Patient Ownership of End Results (EMPOWER) brochure) and at least one brief supportive counselling session by the clinical pharmacist or physician was applied to all eligible patients. All 12 eligible patients consented to benzodiazepine deprescribing; however, only 11 of them (92%) initiated benzodiazepine deprescribing. Six of the 11 patients (55%) had their benzodiazepines discontinued, with the 5 remaining patients (45%) achieving greater than 50% dosage reduction. Seven patients (64%) experienced side effects during the deprescribing process, with over half (57%, n=4) of these seven patients experiencing worsening anxiety symptoms. Five of the 11 patients (45%) required benzodiazepine substitute medications. The use of a structured patient education intervention involving the use of a structured medication review, written patient education material and one-on-one patient counselling can promote benzodiazepine deprescribing. Although worsening anxiety was frequently observed, this was easily managed by the substitution of a more appropriate and clinically indicated medication, which was well tolerated and acceptable by all of our participants. Targeted screening for the presence of anxiety would help to guide the deprescribing process and the need for medication substitution.